Analysis of Determinants of Land and Building Tax (PBB-P2) Compliance with Digital Payment as a Moderating Variable - Fitri, Riana Adesta; Winarto, Tjahjo (Akuntansi dan Teknologi Informasi, 2026)
Purpose – This study aims to analyze the effect of tax payment motivation, trust in government, and digital payment on taxpayer compliance, as well as the moderating role of digital payment, in the context of land and building tax (PBB-P2) compliance. Methods – A quantitative approach was employed using a survey of 100 PBB-P2 taxpayers in Bantul who use digital payment. Data were analyzed using multiple linear regression and Moderated Regression Analysis with Stata 19 SE. Findings - The results show that tax payment motivation, trust in government, and digital payment significantly affect tax compliance. Moreover, digital payment is proven to moderate the effect of motivation on tax compliance. These findings indicate that enhancing motivation and trust in government, supported by the availability of convenient digital payment systems, can improve PBB-P2 tax compliance. Implications - The findings provide practical implications for local governments in optimizing PBB-P2 revenue. Strengthening motivation and public trust, when supported by digital payment facilities, can foster voluntary tax compliance. Originality - This study integrates psychological factors (motivation and trust in government) with technological factors (digital payment) to explain tax compliance. It also introduces digital payment as a moderating variable, which is proven to strengthen the effect of motivation on compliance.